Assessing The Impact of Covid-19 on Financial Distress: A Comparative Study Across Diverse Industries in Malaysia - Muhammad , Kamaruzzaman; Ghani , Erlane K; Hashim, Marshita Binti; Luthan , Elvira (International Journal of Accounting and Economics Studies, 2025)
This study examines the impact of the COVID-19 pandemic on financial distress across nine industries in Malaysia, using the Altman Z-score as the primary measure of financial health. A content analysis was conducted on the annual reports of 80 companies from 2018 to 2021, with a focus on 2021 to capture the extended effects of the pandemic. ANOVA was used to identify significant differences in mean Z-scores between industries, followed by post hoc tests to determine which sectors exhibited the most significant variation. Paired-samples t-tests were used to examine intra-industry changes over time. The average Z-score across all companies was 5.81, indicating generally low bankruptcy risk. However, sectoral differences were evident. The healthcare industry emerged as the most resilient, with a high average Z-score of 10.76, driven by increased demand, government support, and investor confidence. Conversely, the telecommunications sector recorded the lowest score of 3.83, indicating moderate risk. The results highlight the uneven financial impact of the pandemic and emphasize the need for industry-specific financial strategies. The findings contribute to the existing literature on financial distress in emerging markets and provide practical insights for policymakers and business leaders to improve financial resilience in preparation for future crises.